Evi5 promotes collective cell migration through its Rab-GAP activity. - Laflamme, C.; Assaker, G.; Ramel, D.; Dorn, J.F.; She, D.; Maddox, P.S.; Emery, G. (Journal of Cell Biology, 2012)
Membrane trafficking has well-defined roles during cell migration. However, its regulation is poorly characterized. In this paper, we describe the first screen for putative Rab-GTPase-activating proteins (GAPs) during collective cell migration of Drosophila melanogaster border cells (BCs), identify the uncharacterized Drosophila protein Evi5 as an essential membrane trafficking regulator, and describe the molecular mechanism by which Evi5 regulates BC migration. Evi5 requires its Rab-GAP activity to fulfill its functions during migration and acts as a GAP protein for Rab11. Both loss and gain of Evi5 function blocked BC migration by disrupting the Rab11-dependent polarization of active guidance receptors. Altogether, our findings deepen our understanding of the molecular machinery regulating endocytosis and subsequently cell signaling during migration.